2017
DOI: 10.1042/bsr20171059
|View full text |Cite
|
Sign up to set email alerts
|

Busulfan administration produces toxic effects on epididymal morphology and inhibits the expression of ZO-1 and vimentin in the mouse epididymis

Abstract: Busulfan is an alkane sulphonate currently used as an anticancer drug and to prepare azoospermic animal models, because it selectively destroys differentiated spermatogonia in the testes. However, few studies have focussed on the exact effects of busulfan treatment on the epididymis currently. The present study assessed the effect of busulfan on epididymal morphology and the blood–epididymis barrier in mice. We treated mice with a single injection of busulfan and detected the effect at different time points. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…However, corroborating with a previous report (Fang et al, 2017), tDFI assay revealed that busulfan caused a high level of DNA damage in epididymal spermatozoa in the rats. There was also heightened sperm DNA damage due to oxidation, as evident by a significant rise in 8OHdG levels.…”
Section: Discussionsupporting
confidence: 92%
“…However, corroborating with a previous report (Fang et al, 2017), tDFI assay revealed that busulfan caused a high level of DNA damage in epididymal spermatozoa in the rats. There was also heightened sperm DNA damage due to oxidation, as evident by a significant rise in 8OHdG levels.…”
Section: Discussionsupporting
confidence: 92%
“…The tight junction protein ZO-1 regulated cell proliferation and gene expression (Georgiadis et al, 2010). Occludin was associated with the formation of epididymal tight junctions (Long et al, 2017;Fang et al, 2017). Vim provided physical support to the BTB and mainly contributed to controlling cell shape changes and cell mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used busulfan as a positive control. Busulfan is a common alkylating drug for chronic myeloid leukemia that is widely used before the transplantation of hematopoietic stem cells 31,32 and has been categorized in a high-risk group in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used busulfan as a positive control. Busulfan is a common alkylating drug for chronic myeloid leukemia that is widely used before the transplantation of hematopoietic stem cells 31,32 and has been categorized in a high‐risk group in previous studies. We used two doses of NCL1: a high dose of 3.0 mg/kg, and a low dose of 1.0 mg/kg,the latter was previously reported by us as a therapeutic dose 12 .…”
Section: Discussionmentioning
confidence: 99%